Release of dengue virus genome induced by a peptide inhibitor. - Shee-Mei Lok; Joshua M Costin; Yancey M Hrobowski; Andrew R Hoffmann; Dawne K Rowe; Petra Kukkaro; Heather Holdaway; Paul Chipman; Krystal A Fontaine; Michael R Holbrook; Robert F Garry; Victor Kostyuchenko; et al. (PLoS ONE, 2012)
Dengue virus infects approximately 100 million people annually, but there is no available therapeutic treatment. The mimetic peptide, DN59, consists of residues corresponding to the membrane interacting, amphipathic stem region of the dengue virus envelope (E) glycoprotein. This peptide is inhibitory to all four serotypes of dengue virus, as well as other flaviviruses. Cryo-electron microscopy image reconstruction of dengue virus particles incubated with DN59 showed that the virus particles were largely empty, concurrent with the formation of holes at the five-fold vertices. The release of RNA from the viral particle following incubation with DN59 was confirmed by increased sensitivity of the RNA genome to exogenous RNase and separation of the genome from the E protein in a tartrate density gradient. DN59 interacted strongly with synthetic lipid vesicles and caused membrane disruptions, but was found to be non-toxic to mammalian and insect cells. Thus DN59 inhibits flavivirus infectivity by interacting directly with virus particles resulting in release of the genomic RNA.